The Impact of Mobile Technology on Consumers’ Charitable Behaviors: a Research Protocol - Agourram, Hasna; Agourram, Hafid (European Scientific Journal, ESJ, 2022)
Mobile sales have increased over the past decade. In today’s online retail environment, the mobile channel has the added potential to bring greater value to the retail value chain. While researchers have examined a number of factors contributing to the success of mobile technology in the context of for-profit businesses, the benefits of the mobile channel remain largely untapped by organizations in the third sector – those outside the public and private sectors. Such organizations known as non-profits include voluntary and community organizations, cooperatives, and registered charities. Focusing specifically on charities, this article explores the impact of mobile technology on individuals’ charitable intentions. Because the design of mobile apps influences both usability and functionality, we believe that their successful implementation can help charities not only increase their visibility but also attract more donations. This research proposes the use of the color green in a mobile app as a way to improve user browsing time on the charity’s application. It is also proposed that the best time to target donors (existing and potential) is when they go to bed, otherwise known as “bedtime”. Accordingly, the use of the color green in the conceptualization of a charity’s mobile app significantly improves the user’s attention when navigating the app and ultimately positively affects their intention to donate. To illustrate this research protocol, we developed a conceptual framework for improving donation behavior; this framework will be tested through online studies. This research proposal has the potential to add much to the existing literature on multi-channel marketing and, in particular, on the impact of the mobile channel on consumers’ donation behaviors towards charitable organizations.